Toward promoting resilience of gender and sexually diverse youth in South African rural school ecologies - Zhange, Mthandeki; Mohangi, Kamleshie (Frontiers in Education, 2024)
Introduction Gender and sexually diverse youth in schools experience exclusion, which detrimentally affects their ability to cope with the consequences of minority stress and may lead to absenteeism or dropout. The purpose of the study is to highlight a pressing need for inclusive policies and practices to aid in enabling LGBTQ+ learners in schools. Methods This paper explores how multiple systems intersect to promote a sense of inclusion and engagement within the school environment and impact the resilience of LGBTQ+ youth in a rural school setting. This paper presents findings from a qualitative interpretive phenomenological study with twelve purposively selected self-identifying LGBTQ+ youth residing in a rural South African community. Data was gathered through semi-structured interviews. Results This study shows the significance of teacher emotional support, addressing homophobic bullying, moving away from gender-based uniform prescriptions and designating some school bathrooms as gender-neutral to LGBTQ+ learners' resilience. Conclusion The findings of this study demonstrate how certain schools in rural settings employ innovative methods to support LGBTQ+ learners despite limited resources and the absence of comprehensive, inclusive policies on gender and sexually diverse learners. The findings have implications for LGBTQ+ learners in rural community schools worldwide. Future longitudinal studies could focus on how school ecologies inclusive of teachers, parents and the wider community can foster the resilience of LGBTQ+ learners, particularly in rural community contexts.